(3LGeY GdeYGQa hGdCMcGes - (3GdMSjfj, GdcGXej, oTnqHQ, GdeLdSj GdKGfj, YHO Gddg Hf eMeO QVG Bd THQ, J (B1242(3g`s ((3HNW eDdagGs)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hGdUdGI hGdSdGe Ydi eMeO hBdg GdWGgQjf(B...(3CeG HYO agPG gh GdeLdO GdSGOS ef cJGH LGeY GdTQGFY hGdCMcGe aj eYQaI GdMdGd hGdMQGe(B...s
(3BNQgG (B:s
(3QLd MVQJg GdhaGI abGd(B: (3dadGf YfOj Cda OQge EdG bdjdG, ce Gdbdjd? Gdbdjd gh GdfUa dbhdg JYGdi (B{ (3jG CjgG GdeRed be Gddjd EdG bdjdG fUag (B} (3HGdCKQ Yf GdQVG (B- (3Ydjg GdSdGe (B- (3bO Je hced cJGH GdeYGedGJ(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B:(3L(B2(3,U(B279s
(3GdPQjYI(B:(3L(B5(3,U(B50(3,Qbe(B281s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis